Corrosion inhibition efficiency of some hydrophobically modified chitosan surfactants in relation to their surface active properties - Ahmed M. Alsabagh; Maher Z. Elsabee; Yasser M. Moustafa; Alzahraa Elfky; Rania E. Morsi (Egyptian Journal of Petroleum)
This work deals with surface activity and corrosion inhibition efficiency of the natural polymer chitosan and its hydrophobically modified derivatives (eight polymeric compounds). Chitosan was found to be inactive at interfaces but the hydrophobic modification using different aliphatic and aromatic substituents renders the products surface active polymers. From the obtained data it was found that the surface active properties increased by increasing the hydrophobic character of these polymers. Chitosan and its based surfactants were investigated as corrosion inhibitors for carbon steel in 1 M HCl solution using the potentiodynamic polarization method. The resulted corrosion inhibition efficiency situated between 67.56% and 93.23% at 250 ppm and 25 °C. The inhibition efficiency was discussed on the light of surface active properties and the chemical structure of the used derivatives. The quantum chemical calculations were performed for some chitosan derivatives. The charge density distribution, highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO), and dipole moment were considered.